SISTEM KEAMANAN RUMAH BERBASIS IOT DENGAN SMARTLOCK - Haeruddin; Gautama Wijaya; Leo (P3M Institut Teknologi Pagar Alam, 2023)
Security systems are important because they help protect people and things from being hurt or stolen. The development of technology is getting faster and faster and helping people to meet their needs more easily. The house is one of the things that needs to be protected, because the house is a place to take shelter and store valuables and daily necessities. One of the main access to the house is the door. With the development of IoT technology, it can implement a smartlock security system. The security system uses face recognition based on Arduino Uno using face recognition as input. So that the rate of loss, exchange of goods, documents becomes less because only a few users can open them. The output generated by this system is in the form of an electric motion from the door lock and LED as information when face recognition is read. With the existence of a smartlock with face recognition technology that utilizes Arduino Uno, and can provide telegram notifications to homeowners. So that homeowners can monitor the situation of the house in real time.